2020
DOI: 10.1080/21505594.2020.1802193
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicles produced by Burkholderia cepacia cultured with subinhibitory concentrations of ceftazidime enhance pro-inflammatory responses

Abstract: Burkholderia cepacia: is an opportunistic pathogen that infects patients with debilitating underlying diseases. This study investigated the production of outer membrane vesicles (OMVs) by B. cepacia cultured with sub-minimum inhibitory concentrations (MICs) of antibiotics and examined their pathogenic roles both in vitro and in vivo. B. cepacia ATCC 25416 produced more OMVs under antibiotic stress conditions than controls. OMVs isolated from B. cepacia cultured in Luria-Bertani (LB) broth (OMVs/LB) induced cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The study revealed a significant cell lysis/death at 12 and 24 hours following in vitro exposure of RTgill-W1 cells to 12.5 μg/mL OMVs. Consistently, Burkholderia cepacia OMVs induced cytotoxicity in host cells treated with ≥10 μg/mL of OMVs for 24h [55]. In addition, OMVs induced cytotoxicity of the salmonid CHSE-214 cells [13].…”
Section: Conservation Of De Srnas In 65 Strains With Variable Degree Of Virulencementioning
confidence: 60%
“…The study revealed a significant cell lysis/death at 12 and 24 hours following in vitro exposure of RTgill-W1 cells to 12.5 μg/mL OMVs. Consistently, Burkholderia cepacia OMVs induced cytotoxicity in host cells treated with ≥10 μg/mL of OMVs for 24h [55]. In addition, OMVs induced cytotoxicity of the salmonid CHSE-214 cells [13].…”
Section: Conservation Of De Srnas In 65 Strains With Variable Degree Of Virulencementioning
confidence: 60%
“…Acinetobacter baumannii is becoming epidemic in the hospital. The source of these microorganisms is soil and green grass and they become very aggressive with the overuse of broad-spectrum antibiotics and consequently causing serious wound infections that show drug resistance to various types of antibiotic [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the nature and sebum oily niche of C. acnes , common proteins involved in lipolysis such as lysophospholipase and triacylglycerol lipase, were identified in the EVs. Although these enzymes are generally considered putative virulence factors, lipases are necessary for C. acnes to maintain healthy skin by metabolizing sebum and releasing fatty acids, which are necessary to keep a proper skin acidity that acts as a natural barrier against harmful pathogens, providing innate skin immunity (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%